If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(r + -7) + -1(r + -8) = 3 Reorder the terms: 2(-7 + r) + -1(r + -8) = 3 (-7 * 2 + r * 2) + -1(r + -8) = 3 (-14 + 2r) + -1(r + -8) = 3 Reorder the terms: -14 + 2r + -1(-8 + r) = 3 -14 + 2r + (-8 * -1 + r * -1) = 3 -14 + 2r + (8 + -1r) = 3 Reorder the terms: -14 + 8 + 2r + -1r = 3 Combine like terms: -14 + 8 = -6 -6 + 2r + -1r = 3 Combine like terms: 2r + -1r = 1r -6 + 1r = 3 Solving -6 + 1r = 3 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 1r = 3 + 6 Combine like terms: -6 + 6 = 0 0 + 1r = 3 + 6 1r = 3 + 6 Combine like terms: 3 + 6 = 9 1r = 9 Divide each side by '1'. r = 9 Simplifying r = 9
| 7+25=18+x | | X-3+2x=x+5 | | 7(4x-2)=5(2-x) | | x+25+x+-5=90 | | (2.4)(2.0)=(X)(0.5) | | 2(3.14)14= | | -(x+8)=-9x+56 | | (2c+5)(c+4)=0 | | 7+3y=18+x | | 3e-x-1=5 | | -16x^2+80= | | log(y)=1.9747log(x) | | 69x+9y=900 | | y=x^2+49 | | 6z-12z=1-18 | | 11n+9=6n+44 | | (9*4)-5=9*(4-5) | | -6h+4=-10h+16 | | 10p(4/5p) | | 5x+10-3x-3= | | y=4x^2+12x-5 | | -8x-18=-146 | | 4t-2=6t+6 | | -16x^2+80x= | | -5x*2x= | | x=1.8*x+32 | | 2x+14=-6x+34 | | a(n)=12+(n-1)(3) | | -6h+4=-10h+6 | | log(6x+12)=1+log(x-6) | | -2-y=-8(2+y) | | X*4+200=x*14-20 |